“Concept” in Modern Linguistics. - Ismatullayeva, Iroda (Журнал иностранных языков и лингвистики, 2023)
The given article discusses concept and conceptualization as the main task in cognitive linguistics. The author shows some features of the concept and shows its peculiarities. Lexical meanings are closely related to concepts. The author states that concepts that have only subjective and occasional nominations without the name of concept and supports his idea with examples.